Factors that Impact on Bystander Cardiopulmonary Resuscitation Performance During the Emergency Ambulance Call for Out-of-hospital Cardiac Arrest - Aldridge, Emogene Sarah (Curtin University, 2024)
A series of five studies exploring the factors that impact on bystander cardiopulmonary resuscitation (CPR) performance during the emergency call for out-of-hospital cardiac arrest. The first study was a scoping review which established that there were significant gaps in the literature regarding barriers to CPR continuation. The second and third studies explored the barriers to CPR initiation and continuation, and the last two explored the strategies call-takers use to overcome these barriers.